Histamine: a potential cytoprotective agent to improve cancer therapy? - Martinel Lamas, Diego José (2015)
Chemotherapy along with radiotherapy is a major treatment of medical oncology. Despite their therapeutic effects achieving local tumor control and in many cases controlling metastasis, both approaches can produce serious adverse effects to normal tissues either immediately or during the long term after treatment. Thus, their related toxicity frequently outweigh clinical benefits and worsen patient's quality of life.Regardless of the high incidence of cancer therapy-associated adverse reactions (e.g., hepato, hemato and cardio toxicities) and their significant impact on morbidity, mortality and health economics; as far as we know, there are no standard, clinically approved, effective agents that could improve the therapeutic index of chemo and radiotherapy, controlling these devastating side effects in patients undergoing anti-tumoral treatments.1, 2 Therefore, the development of pharmacological approaches to effectively prevent conventional cancer therapy-induced toxicity is of utmost importance.